An open‐label pilot study of N‐acetylcysteine for skin‐picking in Prader–Willi syndrome. Issue 2 (5th December 2013) - Miller, Jennifer L.; Angulo, Moris
ABSTRACT Prader–Willi syndrome (PWS) is a complex neurodevelopmental disorder caused by an abnormality on the long arm of chromosome 15 (q11‐q13) that results in a host of behavioral characteristics including excessive interest in food, skin picking, difficulty with a change in routine, and obsessive and compulsive behaviors. Skin‐picking can result in serious and potentially life‐threatening infections. Recent evidence suggests that the excitatory neurotransmitter glutamate is dysregulated in obsessive‐compulsive behaviors, and modulation of the glutaminergic pathway may decrease compulsive behaviors, such as recurrent hair pulling or skin‐picking behaviors. N‐acetylcysteine (NAC), a derivative of the amino acid cysteine, is thought to act either via modulation of NMDA glutamate receptors or by increasing glutathione in pilot studies. Thirty‐five individuals with confirmed PWS (ages 5–39 years, 23 females/12 males) and skin‐picking behavior for more than 1 year were treated with N‐acetylcysteine (Pharma‐NAC®) at a dose of 450–1, 200 mg/day. Skin‐picking symptoms and open lesions were assessed after 12 weeks of treatment by counting and measuring lesions before and after the medication. All 35 individuals had improvement in skin‐picking behaviors. Ten (29%) individuals (six males and four females) did not have complete resolution of skin‐picking behavior, but had significant reduction in the number of active lesions. Longer‐term, placebo‐controlled trials are needed to further assess the potential benefit of this treatment. © 2013 Wiley Periodicals, Inc.